Association between triglyceride-cholesterol-body weight index and sarcopenia in the older adults from China: A cross-sectional study - Yanmei Ning; Doudou Li; Ting Zhang; Jiana Shi; Ying Hu (PLoS ONE, 2026)
Background The triglyceride-cholesterol-body weight index (TCBI) is a simple and reliable indicator of nutritional status. This investigation aimed to explore the association between TCBI and sarcopenia among older individuals in China. Methods The AWGS 2019 criteria were utilized to evaluate sarcopenia. TCBI was calculated as (TG × TC × BW)/1000. Logistic regression analysis explored the independent connection between TCBI and the occurrence of sarcopenia. RCS was employed to investigate both linear and nonlinear correlations, and threshold effects were scrutinized. Furthermore, subgroup and sensitivity analyses were also conducted. Results This study included 5293 participants. The TCBI was found to be negatively associated with sarcopenia in a fully corrected model, with a 66% decrease in the prevalence of sarcopenia for each 1-unit increase in LgTCBI (OR = 0.34; 95% CI: 0.28–0.41; p < 0.001). The study showed that this association was further highlighted in those with normal BMI and remains consistent in sensitivity analyses. Furthermore, we found a nonlinear association between both TCBI and sarcopenia, with an inflection point of 7.05 by the RCS curve and threshold effect analysis. Conclusion This study revealed a nonlinear negative correlation between TCBI and sarcopenia, highlighting the implications of these findings for the early screening and timely intervention of sarcopenia.